SINTESIS DAN KARAKTERISASI PIGMEN HEMATIT (α-Fe2O3) DARI BIJIH BESI ALAM MELALUI METODE PRESIPITASI - Kukuh Dwi Septiana; Priyono Priyono; Nurul Taufiqu Rochman; Yuswono Yuswono; Tito Prastyo Rahman; Dwi Wahyu Nugroho; Radyum Ikono; Nofrizal Nofrizal; Nurwenda Novan Maulana (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
Indonesia has a lot of mining material of iron ore that could be used for various purposes in the steel industry or for pigment manufacturing. This research, has synthesized the Hematite (α-Fe2O3) pigment manufacture through a precipitation mechanism. The iron ore powder is mixed with HCl and NH4OH, then it is dried at a temperature of 150oC and calcinated at a temperature of 500oC and 800oC for knowing the formation temperature of α-Fe2O3 crystal’s structure. Next, the synthesis results are characterized with XRD at 2θ from 10o to 80o with a sampling pitch of 0,02o. Synthesis results show that the raw material has a lattice parameter values a = b = 5,017 Ǻ and c = 13,652 Ǻ after purifying, the values of lattice parameter become a = b = 5,030 Ǻ and c = 13,739 Ǻ which appropriate with standard of ICDD No. 33-0664. The crystallite size is at range of 40 nm while the lattice strain at 1,700 x 10-4 to 3,500 x 10-4. The results of the color test indicate calcination value L * a * b * = 28,36, 27,86, 30,24 at temperature of 500oC where as at 800oC of the calcination temperature obtain values L * a * b * = 20,47, 22,42, 18,17.Keywords: iron ore, pigments, α-Fe2O3, precipitation